The association between soluble intercellular adhesion molecule-1 levels in drained dialysate and peritoneal injury in peritoneal dialysis. (1st January 2017) - Igarashi, Yusuke; Morishita, Yoshiyuki; Yoshizawa, Hiromichi; Imai, Reika; Imai, Toshimi; Hirahara, Ichiro; Akimoto, Tetsu; Ookawara, Susumu; Ishibashi, Kenichi; Muto, Shigeaki; Nagata, Daisuke
Abstract: Background: Chronic inflammation of the peritoneum causes peritoneal injury in patients on peritoneal dialysis. Intercellular adhesion molecule-1 and its circulating form, soluble intercellular adhesion molecule-1, play pivotal roles in inflammation. However, their role in peritoneal injury is unclear. Methods: We measured changes in intercellular adhesion molecule-1 expression in the peritoneum of a peritoneal injury model in rats. The associations between soluble intercellular adhesion molecule-1 levels in drained dialysate and the solute transport rate (D/P-Cr and D/D0-glucose) determined by the peritoneal equilibration test, and matrix metalloproteinase-2 levels in drained dialysate were investigated in 94 peritoneal drained dialysate samples. Results: Intercellular adhesion molecule-1 expression was increased in the peritoneum of rats with peritoneal injury. Soluble intercellular adhesion molecule-1 levels in drained dialysate were significantly positively correlated with D/P-Cr ( r = .51, p < .01) and inversely correlated with D/D0-glucose ( r = −.44, p < .01). They were also significantly positively correlated with matrix metalloproteinase-2 levels in drained dialysate ( r = .86, p < .01). Conclusions: Intercellular adhesion molecule-1expression is increased in the peritoneum of a peritoneal injury model in the rat, and soluble intercellular adhesion molecule-1 levels in drained dialysate are associated with peritoneal injury in patients on peritoneal dialysis. These results suggest that soluble intercellular adhesion molecule-1 could be a novel biomarker of peritoneal injury in patients on peritoneal dialysis.